Comparison of Diazinon Toxicity to Temperate and Tropical Freshwater Daphnia Species - Thanh-Luu Pham; Ha Manh Bui (Journal of Chemistry)
The presence of pesticides in water bodies presents unique challenges to the ecosystem and all the life forms. Biological methods have been widely used to examine the toxic effects of various toxicants including pesticides. The present study aims at determining the adverse effects of diazinon, a nonsystemic organophosphate insecticide, on two cladoceran species including the temperate Daphnia magna (D. magna) and the tropical Daphnia lumholtzi (D. lumholtzi). The 48 h LC50 values demonstrated higher toxicity of diazinon for D. lumholtzi at a concentration of 3.41 µg·L−1 compared to D. magna at a concentration of 4.63 µg·L−1. After 14 days of exposure to diazinon, the survival capacity as well as the reproduction potential of the two cladoceran species clearly reduced and their rate of population increase (RPI) decreased at concentrations >0.1 µg·L−1. The present study indicated that the tropical cladoceran (D. lumholtzi) was more sensitive than the temperate D. magna. Therefore, it could be used as an indicator for toxicity assessment in tropical environments. The presence of diazinon in water bodies can be associated with significant risk to aquatic organisms.